Polypoid gastric cancer - Belo-Oliveira, P (2005)
A 60-year-old male presented to the emergency room with a postprandial abdominal pain, vomiting, anorexia and weight loss. An epigastric mass could be felt on examination, and the laboratory test values confirmed that he had anaemia.